Still Waiting for Madame President: Hillary Clinton and the Oval Office - Goddard, Joe (Academic Quarter | Akademisk kvarter, 2013)
This essay investigates gender in politics through the prism of Hillary Clinton’s 2008 campaign for the Democratic nomination. It looks at the reactions to that campaign in the media, both in 2008 and as a probable second Clinton campaign emerges for 2016. Topics explored include whether the reactions to Clinton’s campaigns are generic or specific to Clinton herself, and whether gender remains a limiting force in American political life.